Etnobotani tanaman di lanskap Pura Luhur Batukaru dan Pura Luhur Uluwatu, Bali - Anak Agung Keswari Krisnandika; I Dewa Gede Agung Surya Pranditha; Ni Wayan Febriana Utami; Ikhsan Noviady (Jurnal Arsitektur Lansekap, 2025)
Differences in socio-cultural conditions and landscapes of an area can cause differences in the types of plants cultivated. This ethnobotanical study aims to inventory, map, and document various types of plants and their relationships with humans for cultural conservation purposes. The survey method was used to inventory plant types in Batukaru Temple (mountains) and Uluwatu (hills) as well as the yards of residents in both villages. The results of the study showed that plants cultivated in the Batukaru Temple area and the yards of residents of Wongaya Gede Village have a low level of similarity (Sorensen index 0.2) with plants in the Uluwatu Temple area and the yards of residents of Pecatu Village. However, the use and preferences of the community towards plants are more directed towards aesthetic functions compared to other functions such as rituals, medicine, and consumption. Codiaeum variegatum, Bougainvillea glabra and Plumeria sp. are plants with high frequencies and are found in both areas.